A Survey of Professional Training and Certification of Rural Administrators and Rural Teachers in New Mexico - Tingley, Wayne ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1986)
Teachers and administrators in rural New Mexico schools and preservice teachers at New Mexico State University were surveyed to determine components that could be included in teacher education programs to augment prospective rural teachers' skills and to ease problems of recruitment/retention of certified personnel in rural schools. Questionnaires from 169 rural public elementary/secondary school teachers provided information on experience, certification, training, teaching conditions, and ways of staying up-to-date professionally. Questionnaires from 16 administrators addressed preparation for administering rural schools, teaching/administrative experience, staying professionally current, and acquisition and retention of certified teachers. Opinionnaires from 108 preservice teachers addressed adequacy of teacher training for rural educators, students' perceptions of rural schools, number of credits earned in specialties, and professional development. The study found that: 98.2% of teachers and 75% of administrators were certified, rural educators tended not to be transient, certification requirements did not adversely affect rural educators, 43.8% of the respondents taught multigrade classes, and 54.4% of respondents felt teacher training prepared them for rural teaching. Data on the surveyed population, schools, and professional characteristics are presented in summary and tabular form. Questionnaires and lists of school districts form the appendix. (LFL)
ERIC Note: Ph.D. Dissertation, New Mexico State University.
Educational level discussed: Elementary Secondary Education.
Educational level discussed: Higher Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Administrator Education; Administrator Qualifications; Elementary Secondary Education; Higher Education; Preservice Teacher Education; Public Schools; Questionnaires; Rural Education; Rural Schools; Student Teacher Attitudes; Teacher Background; Teacher Education; Teacher Education Curriculum; Teacher Education Programs; Teacher Recruitment; Teaching Conditions; Teaching Experience; New Mexico; Dissertations/Theses, Doctoral Dissertations; Reports, Research